The Effect of Age and occupation on the Type and the Number of workers injuries in construction sector in Iraq (Journal of Engineering, 2014)
World statistics proved that the most of work dangerous accidents, which causes death, are occurred in the construction works. These accidents related to many causes such as loss of workers experience and ignoring rules of safety requirements, especially young workers. Due to the risk of accidents that may occur in the site of work, the idea of this study crystallized to show the relationship between the age of worker and number of injuries and accidents, to identify the causes of these injuries, and to put the appropriate solutions to avoid or reduce the risk of work injuries. Also, the research shows the main principles of safety requirements to forming a clear picture about the subject of the study. A questioner form was prepared to collect the information and then analyzing it statistically in order to reach to the results and recommendations which contribute to decrease the occurrence of work injuries in the sites of construction projects.